Analisis Pemikiran Al-Ghazali dan Ibnu Miskawaih Tentang Pendidikan Anak - Rachmawati, Suci (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This study examines the comparison of Al-Ghazali and Ibn Miskawaih's thoughts on the concept of children's education and its relevance in the context of contemporary Islamic education. The phenomenon of moral degradation among the younger generation and the tendency of the modern education system to emphasize the cognitive aspect more than the moral and spiritual aspects are the background for the urgency of this research. The purpose of the research is to analyze the concept of children's education according to the two figures, identify the similarities and differences in their thinking, and examine their relevance to the context of contemporary Islamic education. This study uses a narrative-based descriptive qualitative method based on literature study by exploring the primary works of the two figures, namely "Ihya Ulumuddin" by Al-Ghazali and "Tahdzib al-Akhlaq" by Ibn Miskawaih. An in-depth analysis was carried out on the fundamental concepts of children's education put forward by the two Muslim thinkers. The results of the study show that despite the differences in approaches, the two figures emphasize the integration of spiritual, moral, and intellectual aspects in children's education. Al-Ghazali emphasizes the spiritual-sufistic dimension in the formation of children's character, while Ibn Miskawaih uses a philosophical-rational approach in moral development. Their thinking has significant relevance to contemporary education in terms of character education, holistic approaches, constructivistic learning methods, socio-emotional learning, value-based education, and educational personalization. This research contributes to the development of a comprehensive Islamic education model by integrating classical intellectual property to address educational challenges in the digital age and globalization.